Child Access Prevention Laws and Juvenile Firearm-Related Homicides - D. Mark Anderson; Joseph J. Sabia; Erdal Tekin (Institute of Labor Economics (IZA), 2018)
Debate over safe-storage gun regulations has captured public attention in the aftermath of several high-profile shootings committed by minors. Whether these laws actually decrease youth gun violence, however, is an unanswered question. Using data from the FBI's Supplementary Homicide Reports for the period 1985-2013, this study is the first to estimate the relationship between child access prevention (CAP) laws and firearm-related homicides committed by juveniles. Our results suggest that CAP laws are associated with a 19 percent reduction in juvenile firearm-related homicides. The estimated effect is stronger among whites than blacks and is driven by states enforcing the strictest safe-storage standard. We find no evidence that CAP laws are associated with firearm-related homicides committed by adults or with non-firearm-related homicides committed by juveniles, suggesting that the observed relationship between CAP laws and juvenile firearm-related homicides is causal.
Keywords: K4; H7; 330; gun control; child access prevention laws; homicides; crime